Complementary Feeding Patterns and Factors Affecting Timely Introduction in a Tribal Population: A Mixed-Methods Study - Yadav, Surbhi; Ahmad, Shamshad; Lohani, Pallavi; Gahlot, Anju (Indian Journal of Community Health, 2023)
Introduction: About 29-60% of tribal children are underweight due to limited healthcare access. The Kols, a tribe in central India, face similar issues and our study will examine their complementary feeding practices. Methodology: A sequential explanatory mixed-method research design was conducted on 218 Kol tribe women in the Manikpur block of Chitrakoot district Uttar Pradesh. In the first phase, the quantitative interview using a semi-structured questionnaire and in the second phase, an in-depth interview of 20 Kol mothers was conducted using an interview guide. Results: About 52.3% of the women were aged between 26- 35 years, and about 83.9% were illiterate. About half of the children (n=116, 53.5%) were introduced to complementary feed at 6-8 months of age. The independent predictors of the timely initiation of complementary feeding were education (AOR: 2.422, p 0.037), age of the mothers (AOR: 1.2106, p 0.047) and the number of children of the mothers (AOR: 2.715 p 0.004) diet diversity was rarely maintained. Conclusion: Complementary feed was introduced timely for half of the tribal women but diet diversity was not maintained. Health education and counselling to utilize locally available food items should be encouraged.